The growth of three teak (Tectona grandis) clones and its effect on wood properties - Gudiwidayanto Sapto Putro; Sri Nugroho Marsoem; Joko Sulistyo; Suryo Hardiwinoto (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Putro GS, Marsoem SN, Sulistyo J, Hardiwinoto S. 2020. The growth of three teak (Tectona grandis) clones and its effect on wood properties. Biodiversitas 21: 2814-2820. Various clones of superior teak (Tectona grandis L. f.) trees have recently been introduced in several land conditions. A study was conducted on three different clones of superior teak known as Jati Unggul Nusantara (JUN) growing in Paliyan, Gunungkidul, Yogyakarta, Indonesia. Two different ages of those clones were observed their growth rate and its wood properties. Strip plot design was applied to the treatment of tree age (five and eight-year-old) and clone types (D14, F35, and F21 clones). Tree growth was measured on 300 trees, meanwhile, annual growth rate and wood properties were measured on 18 trees. The result showed that at five-year-old as well as eight-year-old, the D14 clone has the best growth performance with diameter of 14.6 ± 1.80 cm and 20.5 ± 2.54 cm and height of 9.8 ± 1.72 m and 15.2 ± 2.13 m respectively. The growth rate negatively correlated with temperature and had no significant correlation to the precipitation. Different clones and tree age significantly affect the variability of fiber length, green specific gravity, and heartwood proportion. The clone of D14 produced the highest-fiber length, green specific gravity, and heartwood proportion (1.111mm; 0.50 and17.7%) at five-year-old trees and (1.156 mm; 0.54 and 49.0%) at eight-years-old.